Analysis of sexual assault evidence by desorption electrospray ionization mass spectrometry. (18th June 2013) - Mirabelli, Mario F.; Chramow, Alexander; Cabral, Elaine C.; Ifa, Demian R.
Abstract : Desorption electrospray ionization mass spectrometry (DESI‐MS) is employed in the forensic analysis of chemical components present in condoms and imaging of latent fingerprints as circumstantial evidence of sexual assault. Polymers such as nonoxynol‐9, polyethylene glycol, and polydimethylsiloxane, as well as small molecules additives such as N ‐methylmorpholine, N ‐octylamine, N, N ‐dibutyl formamide, and isonox 132, commonly used in lubricated condom formulations, were successfully characterized by DESI. The results suggest that DESI‐MS is useful for identification of this type of evidence, and it has advantages over conventional extractive techniques, in terms of speed of analysis and ease of use. Copyright © 2013 John Wiley & Sons, Ltd.